The Effectiveness Of Criminal Sanctions Imposed On Legal Entities In Law Enforcement In Indonesia - Ida Bagus Bayu Brahmantya (Green Publisher Indonesia, 2024)
In Indonesia, legal entities can be subject to criminal sanctions for violations of the law which are regulated in various laws and regulations. The aim of this research is to investigate the effectiveness of implementing criminal sanctions against legal entities in law enforcement in Indonesia. The research method used is normative legal research. Data will be collected through literature studies, analysis of legal documents, and case studies related to the application of criminal sanctions against legal entities in Indonesia. The collected data will be analyzed qualitatively using a descriptive approach and content analysis. The research results show that the effectiveness of implementing criminal sanctions against legal entities in Indonesia is still low. This is caused by several factors, such as unclear laws and regulations, weaknesses in law enforcement, limited resources. This condition results in injustice for society, especially for victims of criminal acts committed by legal entities.